Student Perceptions of English Courses in The Law Department: A Case Study at Nurul Jadid University - Suryanto, Bradhiansyah Tri; Ekaputri, Natasya Amanda; Sari, Silvia Meila (Universitas Nurul Jadid, 2023)
The focus of this study is on how students perceive their prior English-language learning experiences. The study intends to carefully investigate these perceptions in order to provide useful information to university administration and academics. The outcomes are anticipated to act as a basis for well-informed decision-making, helping the institution to raise the standard of English instruction as a whole. This research has the potential to help educators better personalize English learning programs to meet the various requirements and expectations of the students. This study examined the complex web of students' views related to the English learning process using a quantitative descriptive method and survey techniques. The research incorporated a wide range of opinions by polling students enrolled in the Undergraduate Law Study Program at the University of Nurul Jadid who had taken English courses. The third, fifth, and seventh semesters of the law undergraduate study program were the focus of the data collecting, which took place between October 7 and 15, 2023. The findings, revealed in-depth tables, revealed the subtleties of students' perspectives, concentrating on cognitive, affection, and conation aspects inside the English courses of the Nurul Jadid University Law Study Program. Among 21 respondents, 23.8% perceived their understanding as poor, with 33.3% feeling sufficient and another 33.3% considering their understanding good. Only 9.5% felt very good about their grasp of the subject matter, indicating varying levels of comprehension. Regarding affection, 9.5% felt poor, 42.9% felt sufficient, 19.0% felt good, and 28.6% felt very good. Additionally, 9.5% had weak conation, 38.1% had sufficient, and 42.9% had good conation. Identifying factors influencing these aspects is crucial to enhancing student motivation and engagement in English courses.